Adapting Lymphedema Treatment in Patients with a Mental Disability - de Fátima Guerreiro Godoy, Maria; Maria Pereira de Godoy, Lívia; Ocampos Troitino, Rodrigo; Maria Pereira de Godoy, José (Case Reports in Psychiatry, 2017)
Background and Purpose. Mental disability is often characterized by significant limitations in adaptive skills. When this condition is associated with lymphedema, treatment requires greater commitment of the care team. The objective of this study is to report the treatment of lymphedema using only one therapeutic technique, a low-stretch grosgrain stocking. Case Report. We report the case of a 14-year-old mentally challenged female patient with lymphedema of the left leg, motor difficulties, and impaired speech and sight. According to the caregiver, lymphedema was present at birth; however, the patient had not been submitted to specific treatment. Thus, only one technique, an adapted low-stretch grosgrain compression stocking, was proposed as it could be used during daily life activities. The adaptation involved the grosgrain stocking, fastened using eyelets and cord up to the thigh, being sewn onto a pair of cotton shorts. The result was a clinical improvement with reductions in the perimeter and volume due to the compliance of the patient and the family to treatment. Conclusion. The use of a single treatment strategy in the form of a low-stretch stocking in such cases together with the involvement of a multidisciplinary team can lead to good treatment outcomes for chronic lymphedema.